2019
DOI: 10.11604/pamj.2019.33.269.18203
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus prevalence and seasonal distribution post vaccine introduction in Nairobi county Kenya

Abstract: Rotaviruses are one of the leading etiological agents of gastroenteritis in young children, for which a monovalent G1P(8) vaccine has been provided for free in Kenyan since July 2014. The main objective was to estimate the post vaccine prevalence and seasonal distribution of rotavirus diarrhea in children less than 5 years in Nairobi County, Kenya. Rotavirus positive samples were collected from children below 5 years of age in two hospitals within Nairobi County where vaccination status was card-confirmed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(24 reference statements)
2
5
0
Order By: Relevance
“…This reflects a possible and expected effectiveness of rotavirus vaccination in reducing the burden of rotavirus gastroenteritis [ 21 ]. The study findings are similar to that observed in Nairobi Kenya (15.2%) 5 years post vaccination rollout [ 22 ]. Possibly due to effectiveness of the rotavirus vaccine 5 years post introduction in both countries.…”
Section: Discussionsupporting
confidence: 89%
“…This reflects a possible and expected effectiveness of rotavirus vaccination in reducing the burden of rotavirus gastroenteritis [ 21 ]. The study findings are similar to that observed in Nairobi Kenya (15.2%) 5 years post vaccination rollout [ 22 ]. Possibly due to effectiveness of the rotavirus vaccine 5 years post introduction in both countries.…”
Section: Discussionsupporting
confidence: 89%
“…This re ects a possible and expected effectiveness of rotavirus vaccination in reducing the burden of rotavirus gastroenteritis (22). The study ndings are similar to that observed in Nairobi Kenya (15.2%) 5 years post vaccination rollout (23). Possibly due to effectiveness of the Rota virus vaccine 5 years post introduction in both countries.…”
Section: Discussionsupporting
confidence: 86%
“…Estimation of 2-dose vaccine effectiveness in Moldova, especially against severe cases at 84% (95CI: 65% to 93%), is largely compatible with that in other countries with low mortality (in the mortality layers A and B of WHO), namely VE is 85% (95CI: 80% to 88%) based on the overall analysis of 8 studies, including >32,000 participants (17,22).…”
Section: Discussionmentioning
confidence: 59%
“…The major decrease was among vaccinated cohorts children <1 year in the first year and <2 years in the second year after vaccine implementation. In addition, the number of children <5 years old hospitalized with rotavirus decreased significantly, including unvaccinated cohorts, suggesting indirect protection resulting from children's immunization (17).…”
Section: Discussionmentioning
confidence: 99%